Perumusan Kebijakan Pemerintah & Integrasinya dalam Pendidikan Agama Islam - Laila Safitri Siregar; Nur Azizah Matondang; Abdusima Nasution (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study discusses the formulation of government policies and their integration in Islamic education in Indonesia. Islamic education plays an important role in shaping the character, morality, and spirituality of students, therefore requiring proper and directed policies. This study aims to identify the concept of government policy formulation in Islamic education, understand policy integration, explain the policy formulation process, and analyze the implementation and integration of government policies in Islamic education. This research uses a library research method with a qualitative descriptive approach through collecting data from books, journals, and relevant scientific sources. The results show that the formulation of Islamic education policies is carried out through several stages, namely problem identification, agenda setting, policy formulation, policy adoption, implementation, and evaluation. Policy integration is implemented through curriculum integration, institutional integration, character and value integration, as well as the digitalization of Islamic education. Proper policy implementation can create a balance between religious and general knowledge, between tradition and modernity, and between Islamic values and technological development. However, policy implementation still faces various obstacles such as limited human resources, unequal distribution of educational facilities, and weak coordination among institutions. Therefore, synergy between the government, educational institutions, and society is needed so that Islamic education policies can be implemented effectively and sustainably. Keywords: Government Policy, Islamic Education, Policy Integration, Policy Implementation, National Education Abstrak Penelitian ini membahas tentang perumusan kebijakan pemerintah dan integrasinya dalam pendidikan Islam di Indonesia. Pendidikan Islam memiliki peran penting dalam membentuk karakter, moral, dan spiritual peserta didik sehingga memerlukan kebijakan yang tepat dan terarah. Penelitian ini bertujuan untuk mengetahui pengertian perumusan kebijakan pemerintah dalam pendidikan Islam, memahami integrasi kebijakan, menjelaskan proses perumusan kebijakan, serta menganalisis implementasi dan integrasi kebijakan pemerintah dalam pendidikan Islam. Penelitian ini menggunakan metode studi pustaka dengan pendekatan deskriptif kualitatif melalui pengumpulan data dari buku, jurnal, dan sumber ilmiah yang relevan. Hasil penelitian menunjukkan bahwa perumusan kebijakan pendidikan Islam dilakukan melalui beberapa tahapan, yaitu identifikasi masalah, penyusunan agenda, formulasi kebijakan, penetapan kebijakan, implementasi, dan evaluasi. Integrasi kebijakan dilakukan melalui integrasi kurikulum, kelembagaan, nilai dan karakter, serta digitalisasi pendidikan Islam. Implementasi kebijakan yang baik mampu menciptakan keseimbangan antara ilmu agama dan ilmu umum, antara tradisi dan modernitas, serta antara nilai keislaman dan perkembangan teknologi. Namun, pelaksanaan kebijakan masih menghadapi berbagai kendala seperti keterbatasan sumber daya manusia, kurangnya pemerataan fasilitas pendidikan, dan lemahnya koordinasi antar lembaga. Oleh karena itu, diperlukan sinergi antara pemerintah, lembaga pendidikan, dan masyarakat agar kebijakan pendidikan Islam dapat berjalan secara efektif dan berkelanjutan. Kata kunci: Kebijakan Pemerintah, Pendidikan Islam, Integrasi Kebijakan, Implementasi Kebijakan, Pendidikan Nasional